2017
DOI: 10.1038/ncomms15308
|View full text |Cite|
|
Sign up to set email alerts
|

Adenylate kinase hCINAP determines self-renewal of colorectal cancer stem cells by facilitating LDHA phosphorylation

Abstract: Targeting the specific metabolic phenotypes of colorectal cancer stem cells (CRCSCs) is an innovative therapeutic strategy for colorectal cancer (CRC) patients with poor prognosis and relapse. However, the context-dependent metabolic traits of CRCSCs remain poorly elucidated. Here we report that adenylate kinase hCINAP is overexpressed in CRC tissues. Depletion of hCINAP inhibits invasion, self-renewal, tumorigenesis and chemoresistance of CRCSCs with a loss of mesenchymal signature. Mechanistically, hCINAP bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 70 publications
2
66
0
Order By: Relevance
“…In a mouse model of bladder cancer, AK4 shRNA transfection markedly inhibited tumor growth and metastasis compared with that in a scramble control group ( 20 ). AK4 is also a potential oncogene upregulated in metastatic colorectal cancer and exhibiting in vitro oncogenic properties ( 30 ). In addition, withaferin-A was identified as a potential agent for the treatment of metastatic lung cancer that could regulate AK4-associated gene expression ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of bladder cancer, AK4 shRNA transfection markedly inhibited tumor growth and metastasis compared with that in a scramble control group ( 20 ). AK4 is also a potential oncogene upregulated in metastatic colorectal cancer and exhibiting in vitro oncogenic properties ( 30 ). In addition, withaferin-A was identified as a potential agent for the treatment of metastatic lung cancer that could regulate AK4-associated gene expression ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, Jin et al revealed that Y10 phosphorylation elicited LDHA activation, promoting cancer cell invasion and enhancing anoikis resistance. Also in colorectal cancer, Ji et al found that human coilin–interacting nuclear ATPase protein (hCINAP) expression was positively correlated with the level of Y10 phosphorylated LDHA. The molecular mechanism is that hCINAP binds to the C‐terminal region of LDHA and depends on its own adenylate kinase activity to promote phosphorylation of LDHA catalyzed by fibroblast growth factor receptor 1 (FGFR1) at Y10 .…”
Section: Regulation Modes Of Ldhamentioning
confidence: 99%
“…Also in colorectal cancer, Ji et al found that human coilin–interacting nuclear ATPase protein (hCINAP) expression was positively correlated with the level of Y10 phosphorylated LDHA. The molecular mechanism is that hCINAP binds to the C‐terminal region of LDHA and depends on its own adenylate kinase activity to promote phosphorylation of LDHA catalyzed by fibroblast growth factor receptor 1 (FGFR1) at Y10 . Furthermore, Fan et al found that direct phosphorylation of LDHA at Y10 and Y83 significantly enhanced LDHA tetramer formation and cofactor binding, resulting in a significant increase in lactate dehydrogenase activity.…”
Section: Regulation Modes Of Ldhamentioning
confidence: 99%
“…The AK-catalyzed phosphotransfer system plays a key role in the maintenance of energy homeostasis in well-differentiated cells with intermittent high-energy demand, such as neural, cardiac, and skeletal muscle cells [36]. It is upregulated in human CRC [37] with the total AK activity about 2 times higher than surrounding normal tissue [10]. The same was also observed in tumor cells of other histological types [38].…”
Section: Toxicity Of Cpps On Caco-2 Cellsmentioning
confidence: 94%